2020
DOI: 10.1038/s41586-020-2400-z
|View full text |Cite|
|
Sign up to set email alerts
|

A planet within the debris disk around the pre-main-sequence star AU Microscopii

Abstract: AU Microscopii (AU Mic) is the second closest pre-main-sequence star, at a distance of 9.79 parsecs and with an age of 22 million years 1 . AU Mic possesses a relatively rare 2 and spatially resolved 3 edge-on debris disk extending from about 35 to 210 astronomical units from the star 4 , and with clumps exhibiting non-Keplerian motion 5-7 . Detection of newly formed planets around such a star is challenged by the presence of spots, plage, flares and other manifestations of magnetic 'activity' on the star 8,9 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(137 citation statements)
references
References 50 publications
9
124
0
Order By: Relevance
“…K2 Howell et al 2014, TESS Ricker et al 2014& NGTS Wheatley et al 2018) discovering young ( 100 Myr) close-in planets has become possible. Notable recent examples are the four planets in the V1298 Tau system at an age of ∼ 24 Myr (David et al 2019), a ∼ 45 Myr old planet around DS Tuc A (Newton et al 2019), a ∼ 23 Myr old planet around AU Mic (Plavchan et al 2020) as well as other recent results from the thyme project (e.g. Rizzuto et al 2020).…”
Section: Introductionmentioning
confidence: 93%
“…K2 Howell et al 2014, TESS Ricker et al 2014& NGTS Wheatley et al 2018) discovering young ( 100 Myr) close-in planets has become possible. Notable recent examples are the four planets in the V1298 Tau system at an age of ∼ 24 Myr (David et al 2019), a ∼ 45 Myr old planet around DS Tuc A (Newton et al 2019), a ∼ 23 Myr old planet around AU Mic (Plavchan et al 2020) as well as other recent results from the thyme project (e.g. Rizzuto et al 2020).…”
Section: Introductionmentioning
confidence: 93%
“…This modeling should help identify the regions of parameter space that each mass‐loss mechanism dominates. Further, observations of atmospheric escape for the emerging class of very young planets that are the likely antecedents of mature sub‐Neptune size planets (David, Cody, et al., 2019; David, Petigura, et al., 2019; David et al., 2016; Newton et al., 2019; Plavchan et al., 2020; Rizzuto et al., 2020) offer the hope of distinguishing between the photoevaporative and core‐powered atmospheric loss mechanisms. Ultimately, our quantitative insights into how these planets formed, such as the core‐mass function and how much H/He these planets accreted, depend strongly on the assumed mass‐loss model.…”
Section: Future Directionsmentioning
confidence: 99%
“…With the library of all-sky photometry made available by the Transiting Exoplanet Survey Satellite (TESS; Ricker et al 2016), planets around bright young stars have been identified (e.g., Newton et al 2019;E. R. Newton et al 2020, in preparation;Mann et al 2020;Plavchan et al 2020;Rizzuto et al 2020). These are the first planets around bright young stars that are suitable for in-depth characterizations, enabling the first obliquity measurements of newly formed planets (Montet et al 2020;Zhou et al 2020), as well as atmospheric studies in the near future.…”
Section: Introductionmentioning
confidence: 99%